SENTENCE STRUCTURE PROBLEMS AND PARAGRAPH BUILDING IN UNDERGRADUATE STUDENTS’ ACADEMIC WRITING ABILITY - Savina Savina; Soenarjati Djajanegara (INFERENCE: Journal of English Language Teaching, 2022)
The research is conducted to identify issues of sentence structure and paragraph building in academic writing ability. The objectives are to identify the most and the least common problems found in both variables. The data are sixty paragraphs of freshmen of three faculties of a state university in Depok, West Java. Descriptive analysis and Content analysis are the two methods which are used to analyze the data. The findings of the research are divided into two groups: Sentence Structure Problems and Paragraph building problems. For the first category the most common problems are the inappropriate use of Grammar Points, Lexical Units, and Cohesive Device, and the least are Punctuation, Run-On, and Stringy sentences. In the scope of paragraph building, not providing supporting details and irrelevant sentences are the most common problems; as for the least problems are irrelevant sentences and transition sentences.